Individual and Day-to-Day Differences in Active Coping Predict Diurnal Cortisol Patterns among Early Adolescent Girls - Sladek, Michael R. (J Youth Adolesc, 2016)
Prior work has identified alterations in activity of the hypothalamic-pituitary-adrenal axis as a potential mechanism underlying stress-induced emotional health problems, which disproportionately impact girls beginning in mid-adolescence. How adolescent girls differ from one another in dispositional coping tendencies and shift specific coping strategies in response to varying stressors have been theorized as important predictors of their adaptation, health, and well-being during this dynamic period of development. The goal of this study was to examine whether individual and day-to-day (within-person) differences in adolescent girls’ coping responses are associated with daily patterns of hypothalamic-pituitary-adrenal axis activity, indexed by cortisol. Participants were 122 early adolescent girls (M(age) = 12.39) who provided three saliva samples per day for 3 days and completed daily coping reports, as well as a standard coping survey. Participants and primary caregivers also completed objective life stress interviews. On average, girls who were more likely to respond to interpersonal stress with voluntary engagement (active) coping exhibited generally adaptive daily physiological regulation—steeper diurnal cortisol slopes, lower total diurnal cortisol output, and lower cortisol awakening responses. Chronic interpersonal stress level significantly moderated these associations in different ways for two distinct components of the diurnal pattern—the slope and cortisol awakening responses. Regarding within-person differences, using active coping more than usual was associated with higher waking cortisol the following morning, which may help to prepare adolescent girls for perceived daily demands. These findings highlight the interactive influence of stress and coping in the prediction of daily hypothalamic-pituitary-adrenal axis activity and support the stress-buffering role of active coping for adolescent girls.